2002
DOI: 10.1093/cercor/12.5.545
|View full text |Cite
|
Sign up to set email alerts
|

Experience-dependent Modulation of Category-related Cortical Activity

Abstract: Naming pictures of objects from different categories (e.g. animals or tools) evokes maximal responses in different brain regions. However, these 'category-specific' regions typically respond to other object categories as well. Here we used stimulus familiarity to further investigate category representation. Naming pictures of animals and tools elicited category-related activity in a number of previously identified regions. This activity was reduced for familiar relative to novel stimuli. Reduced activation occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
164
2
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(198 citation statements)
references
References 58 publications
(70 reference statements)
31
164
2
1
Order By: Relevance
“…Our work advances our understanding of the processes that mediate adaptive shape recognition beyond previous studies in the following main respects. First, previous functional imaging studies have implicated occipitotemporal and frontoparietal circuits in shape learning (Dolan et al, 1997;Gauthier et al, 1999;Grill-Spector et al, 2000;Chao et al, 2002;Kourtzi et al, 2005;Op de Beeck et al, 2006). However, the indirect, slow hemodynamic response of fMRI limits our understanding of the spatiotemporal brain dynamics that mediate visual form learning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our work advances our understanding of the processes that mediate adaptive shape recognition beyond previous studies in the following main respects. First, previous functional imaging studies have implicated occipitotemporal and frontoparietal circuits in shape learning (Dolan et al, 1997;Gauthier et al, 1999;Grill-Spector et al, 2000;Chao et al, 2002;Kourtzi et al, 2005;Op de Beeck et al, 2006). However, the indirect, slow hemodynamic response of fMRI limits our understanding of the spatiotemporal brain dynamics that mediate visual form learning.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies argue that learning alters early sensory processing (Adini et al, 2002;Teich and Qian, 2003), while others propose that learning alters later decision-related processes (Dosher and Lu, 1999;Li et al, 2004;Law and Gold, 2008;Jacobs, 2009). Previous fMRI studies have implicated both occipitotemporal and frontoparietal circuits in shape learning (Dolan et al, 1997;Gauthier et al, 1999;Grill-Spector et al, 2000;Chao et al, 2002;Kourtzi et al, 2005;Op de Beeck et al, 2006). However, little is known about how learning shapes interactions between these circuits and mediates perceptual improvements in the discrimination of global forms (Scott et al, 2006(Scott et al, , 2008Rossion et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Several previous objectnaming studies were excluded from the meta-analyses. The exclusion criteria were: no non-object baseline [Chao et al, 1999[Chao et al, , 2002Chao and Martin, 2000]; results were only reported in regions of interest rather than for the whole brain [Grabowski et al, 1998;Grafton et al, 1997;Heim et al, 2002;Kan and Thompson-Schill, 2004]; the task was action rather than object naming [Damasio et al, 2001]; and the task was scene identification rather than object naming [Renvall et al, 2003]. …”
Section: Ale Meta-analysismentioning
confidence: 99%
“…Previous studies have compared object-naming activation to reading [Bookheimer et al, 1995;Moore and Price, 1999b], color naming [Price et al, 1996], verbal fluency [Etard et al, 2000], semantic categorization [Tyler et al, 2004], or a range of baselines [Murtha et al, 1999]. Other studies have investigated how the activation pattern changes for overt and covert naming [Zelkowicz et al, 1998], for object category [Chao et al, 1999[Chao et al, , 2002Chao and Martin, 2000;Damasio et al, 1996;Grabowski et al, 1998;Kawashima et al, 2001;Martin et al, 1996;Moore and Price, 1999a;Smith et al, 2001], by scanning modality [Votaw et al, 1999], across languages [Vingerhoets et al, 2003], with name agreement [Kan and Thompson-Schill, 2004], with gender of subjects [Grabowski et al, 2003], and during object learning [van Turennout et al, 2000[van Turennout et al, , 2003. To our knowledge, no previous study has segregated the objectnaming system into its perceptual, semantic, and phonological components.…”
Section: Introductionmentioning
confidence: 99%
“…Initial univariate fMRI studies on object recognition localized selective activation in response to pictures of animate versus inanimate items to distinct portions of fusiform gyrus and lateral occipital cortex (Chao, Haxby, & Martin, 1999;Chao, Weisberg, & Martin, 2002; for review see Martin, 2007). More recently, several fMRI studies using multivariate pattern analysis (MVPA) reported successful decoding of conceptual categories based on picture stimuli from ventral temporal areas (Haxby et al, 2001;Shinkareva et al, 2008).…”
mentioning
confidence: 99%